FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK (Studi Kasus di KPP Pratama Surabaya Mulyorejo) - laura evalina paranoan (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
This study aims to examine the effect of factors that influence taxpayer compliance with the independent variables tax amnesty, tax sanctions and tax audits. This variable was chosen because it is considered to have a major influence on taxpayer compliance in paying taxes for the benefit of a country's development. Where it requires no small amount of funds, but there are still taxpayers who do not report their assets/assets honestly to the state.The population in this study were all individual taxpayers registered at KPP Pratama Surabaya Mulyorejo. The sample is determined by purposive sampling method, namely individual taxpayers who follow registered and must report to KPP Pratama Surabaya Mulyorejo. Based on the research results, it is known that tax amnesty and audit have a significant effect on taxpayer compliance and tax sanctions have no significant effect on taxpayer compliance. This provides information that the existence of a tax amnesty and tax audit can increase taxpayer compliance while tax sanctions have an effect but do not have a major role in increasing taxpayer compliance at KPP Pratama Surabaya Mulyorejo.